Atypical teratoid rhabdoid tumor with intratumoral advancement: significance of active surgical approach in long-term disease (109 months) with metastatic cascade - V. B. Karakhan; E. V. Prozorenko; G. L. Mentkevich; I. S. Dolgopolov; N. V. Sevyan; D. M. Belov (Опухоли головы и шеи, 2022)
The article presents a clinical case of atypical teratoid rhabdoid tumor with one of the longest catamnesis described in literature (109 months) and high quality of life. first, a giant tumor of the frontal lobe with advancement into a lateral ventricle was found in a female patient and totally removed. It was histologically diagnosed as primitive neuroectodermal tumor. Combination treatment consisting of radiotherapy, high-dose polychemotherapy and cellular immunotherapy including intrathecal therapy led to 4-year recurrence-free period. Recurrence of the tumor was resected. The period of the 2nd remission was 34 months. Subsequently, multistage metastasis of the tumor through cerebrospinal fluid tracts of the brain and spinal cord was observed. Twice microsurgical treatment with removal of symptomatic metastases in ventricles Iv and III was performed. In repeat morphological examinations, the tumor was verified as atypical teratoid rhabdoid tumor. The presented clinical case shows the role of active surgical tactics in effective long-term combination treatment of this severe pathology.